Electrocution induced cardiac dysrhythmia: an Izinyoka case - Maritz, Shaan Marthinus; Motsepe, Tshepang Arthur; Gamizelo, Stephane (International Surgery Journal, 2025)
Electrical injuries, although rare, can result in significant morbidity and mortality particularly from cardiac complications. We present a 35-years-old male who developed paroxysmal atrial fibrillation after an electrical shock, had minor burns and no prior cardiac issues. The dysrhythmia resolved during hospitalization and the patient was treated with anticoagulation and wound care before discharge. In South Africa, electrical injuries are commonly seen in patients who attempt illegal connections (Izinyoka) often for socio-economic reasons. While atrial fibrillation is uncommon after electrocution, ECG remains essential for diagnosing dysrhythmias. There is a lack of consensus on the management of electrocution-induced dysrhythmias and further research is needed to develop tailored guidelines for regions with high socio-economic challenges.